2021
DOI: 10.1177/1040638720985563
|View full text |Cite
|
Sign up to set email alerts
|

Serum fibroblast growth factor 23 (FGF-23): associations with hyperphosphatemia and clinical staging of feline chronic kidney disease

Abstract: Fibroblast growth factor 23 (FGF-23) is an independent monitor of the progression of chronic kidney disease (CKD) in human medicine, and FGF-23 may have value as a biomarker in feline CKD. We evaluated the relationship between serum FGF-23 and CKD stages, and the effect of age on FGF-23 in normal cats. We measured FGF-23 and intact parathyroid hormone (iPTH) concentrations by ELISA, with intra- and inter-assay CVs ≤ 15%. The percentage recovery of FGF-23 and iPTH remained stable for up to 7 d in samples stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Because previously published studies [ 22 , 23 , 24 , 25 , 26 ] came with the hypothesis that FGF 23 should increase with increasing SDMA and should be positively correlated to phosphate concentrations, we also evaluated these two parameters. Studies indicate that FGF 23 increases with the progression of CKD in humans, dogs and cats [ 22 , 23 , 24 , 25 ], and therefore could be a biomarker for the early detection of CKD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because previously published studies [ 22 , 23 , 24 , 25 , 26 ] came with the hypothesis that FGF 23 should increase with increasing SDMA and should be positively correlated to phosphate concentrations, we also evaluated these two parameters. Studies indicate that FGF 23 increases with the progression of CKD in humans, dogs and cats [ 22 , 23 , 24 , 25 ], and therefore could be a biomarker for the early detection of CKD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent study investigated the association between a cat’s life stages and serum FGF-23 concentrations and showed that there was no effect of age on FGF-23 in healthy cats. 28 The difference in FGF-23 levels of healthy cats between the studies can be caused by variation of FGF-23 assay rather than age. Thus, the reference interval of feline FGF-23 should be determined per FGF-23 assay.…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of FGF/FGFR targeting therapies is the basis of several preclinical, clinical, and basic investigations. Various nonselective FGF/FGFR inhibitors have been endorsed for cancer or other disease treatment (Degirolamo et al, 2016;Ghedini et al, 2018;Hallinan et al, 2016;Hierro et al, 2015;Lin et al, 2021;Memmos & Papagianni, 2021;Porta et al, 2017;Ronca et al, 2015;Xue et al, 2018), but data highlights a variety of obstacles affecting their use in the clinical practice. It seems required to identify FGF/FGFR alterations and some modifications that may foresee and monitor the response of treatment, to determine the contribution of the FGF/FGFR system in the onset of mechanisms of drug resistance, and to develop effective combinations of FGF/FGFR inhibitors with additional targeted rehabilitations.…”
Section: Future Pharmaceutical Advantage Of Fgf/fgfrmentioning
confidence: 99%